Psychiatry and Cardiovascular Diseases - Şahmelikoğlu Onur, Özge; Günay Arıkan, Ayşe; Goverti, Digdem; Altınkaya, Onur; Şeker, Muhammed Cüneyt; Fedai, Halil; Atılan Fedai, Ülker; Yıldız, Deniz; Yılmaz, Rustem; Öztürk, Hayriye Mihrimah; Öztürk, Selçuk; Baş Uluyol, Özlem; et al. (Academician Publishing Book DOI Portal, 2023)
-